The impact of e-governance on achieving creative performance - حمد, علاء دهام; سعيد, مثنى محمد (Journal of Economics and Administrative Sciences, 2020)
The research aims to investigate the relationship and impact of e-governance as an independent variable in achieving creative performance as a dependent variable. These variables have been studied in the Directorate of Passports Affairs, and seek to come up with a set of recommendations that help in promoting e-governance in the researched organization, and the researcher adopted the descriptive-analytical approach, included The sample (122) of the total (194) individuals distributed in several administrative levels (officers, associates, and administrative staff). By adopting the questionnaire, which included (49) paragraphs as the main tool for the collection of data and information, as well as personal interviews and field observations as a tool to collect them, and for the processing of data and information, the research adopted the program (SPSS V., 24 & AMOS V., 24), the main conclusions The hypotheses have been demonstrated by the importance of the Directorate of Passport Affairs for its creative performance due to its interest in e-governance, especially through possessing the capabilities and human resources, and supporting it in monitoring and evaluation tools, adherence to standards and applications, and managing its financial resources and technology infrastructure.